CHANGE OF EFFECTIVE ENERGY INDEXES OF PNEUMATIC ENGINE OPERATION ASSERDING TO SPEED CHARACTERISTICS - A. Voronkov (Avtomobilʹnyj Transport (Harʹkov), 2015)
The effective indexes of the working process of the pnevmatic engine with an air-distributor valve obtained according to the results of experimental research are presented. The influence of rotation frequency change of the pneumatic engine crankshaft on the value of the torque, power, avarage effective pressure of the rate of effective operation for different values of the inlet compressed air, shown by the change of power of mechanical losses as well as the mechanic ratio, depending on the frequency of pneumatic engine shaft rotation for different values of inlet compressed air pressure.